Phytohormone participation during Citrus sinensis non-host response to Xanthomonas campestris pv. vesicatoria - Petrocelli, Silvana (2018)
Citrus, one of the most valuable fruit crops around the world, are severely damaged by biotic stress and huge economical losses are caused by pathogen infections. Non-host response is an essential plant defense mechanism against pathogen attack, however is still not completely characterized and is poorly studied in non-model plants. In previous reports, we characterized C. sinensis non-host response to Xanthomonas campestris pv. vesicatoria (Xcv), in comparison to infection caused by Xanthomonas citri subsp. citri (Xcc). This was described as a hypersensitive response with structural and physiological modifications, and transcriptional reprogramming of pathogen related proteins and transcription factors, among others. Phytohormones serve as key regulators in plant response to stress, by means of interconnected complex pathways. Here, we study the participation of phytohormone pathways during Citrus non-host response to Xcv. Our results indicate a decrease in abscisic acid, cytokinins, gibberellins, brassinosteroids, auxins and nitric oxide, an increase in ethylene and salicylic acid, constant levels of jasmonic acid, whereas polyamine levels change in a very specific pattern. The present work provides a first broad approach to hormone participation during non-host response in a non-model plant of the Citrus genus, also representative of woody plants.